2011
DOI: 10.3109/15368378.2011.596603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 50 Hz electromagnetic fields on the histology, apoptosis, and expression ofc-Fosandβ-Cateninon the livers of preincubated white leghorn chicken embryos

Abstract: Reports have demonstrated occurrences of abnormalities in the early stages of chicken embryonic development due to the exposure to electromagnetic fields (EMFs). This article was designed to investigate the effects of sinusoidal EMF on the histopathology, apoptosis, and expressions of c-Fos and β-Catenin genes of the livers of preincubated White Leghorn chicken embryos, based on our published experiments. 300 healthy, fresh fertilized eggs were divided into control (n = 70), sham (n = 70), and four experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition, the modulatory effects of celecoxib on transcription levels of c-Fos , a proto-oncogene that turns on a cascade of events that lead to cell division and/or programmed cell death (29,30), disrupt cellular homeostasis. A correlation between low levels of c-Fos transcripts and cell death is reinforced by recent studies using chicken embryos submitted to electromagnetic fields (31). That study reported a strong connection between c-Fos downregulation and cell death in early stages of chicken embryonic development.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the modulatory effects of celecoxib on transcription levels of c-Fos , a proto-oncogene that turns on a cascade of events that lead to cell division and/or programmed cell death (29,30), disrupt cellular homeostasis. A correlation between low levels of c-Fos transcripts and cell death is reinforced by recent studies using chicken embryos submitted to electromagnetic fields (31). That study reported a strong connection between c-Fos downregulation and cell death in early stages of chicken embryonic development.…”
Section: Discussionmentioning
confidence: 89%
“…MF exposure has been reported to affect cell fate in a bimodal fashion, either cytotoxic or cytoprotective [12,13]. To assess whether MF exposure had any effects on cell death or cell viability, FL cells were exposed to a 50-Hz MF at 0.4 mT for 30, 60, or 120 min, then cell early apoptosis and cell viability were determined by Annexin/PI staining and CCK-8, respectively.…”
Section: Mf Exposure Alone Had No Significant Effects On Cell Early Amentioning
confidence: 99%
“…In this study, an increase number of mitochondria were observed in the exposed group at day 10 and day 15. It has been reported that oxidative stress induced by H 2 O 2 leads to increase number of mitochondria and mtDNA in human lung [24]. At day 10 in the exposed group, some of the mitochondria were swollen.…”
Section: Histology and Electron Microscopymentioning
confidence: 83%
“…The embryonic cells rapidly proliferate, differentiate, migrate, and suffer from apoptosis. During these processes, the cells generate electric currents which can be affected by the RFW [24]. This study was designed to observe the effects of electromagnetic field emitted by a mobile phone on rapidly proliferating cells in the developing chicken embryo.…”
Section: Introductionmentioning
confidence: 99%